(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This article analyses the right to health care in Spain from a multilevel perspective. The right to health is guaranteed by the Spanish Constitution, but it has not been interpreted by the Constitutional Court that there is a constitutional obligation to provide free health care to everyone in all cases, which, in the past, led to a situation in which the right to free health care was eliminated, with some exceptions, for some migrants. Spain also has international obligations regarding the right to health, derived from international treaties. The right to free health care is an essential right for the protection of the right to physical integrity and to life and health is a basic need for the lives of peoples without which it is difficult to live and exercise other rights.